PERANCANGAN ARCHITECTURE ENTERPRISE SISTEM INFORMASI MANAJEMEN ASET DI BAGIAN UMUM KOTA BANDUNG (Studi Kasus : SETDA Kota Bandung) - Arif Bakti Nugraha (NUANSA INFORMATIKA, 2020)
Regional Secretary (SETDA) of Bandung City is a local government agency that has the main tasks and functions to Realize Public Services and Excellent Service Personnel to support the Vision of Bandung City as the Superior City of Bandung. The Regional Secretary of the City of Bandung is currently experiencing difficulties in managing information relating to asset investment and management, so it is necessary to strive to manage information better, one form of its application is through information systems using computer-based information technology. In information technology there are three interrelated parts, namely: hardware, software, and database. Integrated information system architecture planning and in accordance with the organization's business goals is one of the efforts to improve services in a better direction so that it is able to compete with other organizations. In this study discusses the planning of information systems architecture management assets in the general section and equipment of the City of Bandung, a case study in the Regional Secretary (SETDA) of the City of Bandung. The discussion of this research is emphasized in four stages, namely: business architecture planning, data architecture planning, application architecture planning, and technology architecture planning. The results of the research conducted are the planning of information systems architecture management in the Regional Secretary of the City of Bandung, in the form of recommendations for the development of information systems architecture to support the improvement of public service performance and system integration into all parts of the organization.Keywords: Business Architecture, Data Architecture, Application Architecture, Technology Architecture, EAP